2017
DOI: 10.1080/13670050.2017.1285862
|View full text |Cite
|
Sign up to set email alerts
|

Bilingual cogito: inner speech in acculturated bilinguals

Abstract: This paper investigates the extent of second language (L2) use in domains belonging to inner speech. The participants consist of 149 highly educated L2-competent sequential Polish-English bilinguals resident in the UK *. The independent variables include acculturation level, social network profile, length of residence, and predicted future domicile. The study combines both quantitative and qualitative approaches. All participants completed an online questionnaire, and 14 of these were also interviewed by the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 37 publications
3
10
0
Order By: Relevance
“…They, on the other hand, reported using the L1 significantly more often in inner speech. This supports Dewaele's findings (2015) and might be linked to Hammer's (2017a) study, the results of which 'showed that acculturation level had a significant effect on frequency of language use in […] inner speech domains' (Hammer 2017a, 13). Even though living in an English-speaking country does not automatically imply high acculturation and bilinguals living in the L2 environment were shown to differ on the level of extent of acculturation (Hammer 2017a(Hammer , 2017b, it is likely that living in an LX-speaking country is generally beneficial in internalising an LX and using it for inner speech.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…They, on the other hand, reported using the L1 significantly more often in inner speech. This supports Dewaele's findings (2015) and might be linked to Hammer's (2017a) study, the results of which 'showed that acculturation level had a significant effect on frequency of language use in […] inner speech domains' (Hammer 2017a, 13). Even though living in an English-speaking country does not automatically imply high acculturation and bilinguals living in the L2 environment were shown to differ on the level of extent of acculturation (Hammer 2017a(Hammer , 2017b, it is likely that living in an LX-speaking country is generally beneficial in internalising an LX and using it for inner speech.…”
Section: Discussionsupporting
confidence: 87%
“…This supports Dewaele's findings (2015) and might be linked to Hammer's (2017a) study, the results of which 'showed that acculturation level had a significant effect on frequency of language use in […] inner speech domains' (Hammer 2017a, 13). Even though living in an English-speaking country does not automatically imply high acculturation and bilinguals living in the L2 environment were shown to differ on the level of extent of acculturation (Hammer 2017a(Hammer , 2017b, it is likely that living in an LX-speaking country is generally beneficial in internalising an LX and using it for inner speech. The interviews additionally showed that naturalistic exposure supports dynamic changes in language internalisation and frequently leads multilinguals 'to think verbally' (Hammer 2017b, 73; see also Guerrero [2009]) in the LX.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Further studies are required to explain these counter-intuitive observations, much in the line of various studies reported in the literature on the neural differences between bilinguals and monolinguals (Marian and Shook, 2012 ; Hammer, 2017 ; Gangopadhyay et al, 2018 ).…”
Section: Feature Extraction and Classificationmentioning
confidence: 96%
“…Due to the static nature of sociobiographical factors and the limitations of linguistic factors in real life use, Pavlenko (2017) urged researchers to concentrate on the specific type and quality of L2 users’ emotional experiences (e.g., opportunities to joke, flirt, date, argue, and fight in L2). The underlying mechanism may be related to Hammer’s (2019) idea that there exist effects of context-specific language selection and use on ‘broader phenomena of frames of reference in the bilingual mind, as well as culturally-specific ways of appraising events’ (p. 14). Also, Dewaele (2013) viewed that the communication of emotion in an LX (a language acquired later in life) can be particularly difficult due to limited means to express the full range of emotions that are appropriate and needed in real communication, and thus he called for future studies on affective socialisation in an LX.…”
Section: Individual Variations In L2 Humour Appreciationmentioning
confidence: 99%